2020
DOI: 10.21203/rs.3.rs-116658/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogens Distribution and Antimicrobial Resistance of Bloodstream Infections at Twenty-Five NICUs in Eastern China, 2016-2019

Abstract: ObjectivesTo describe pathogens distribution and their antimicrobial resistance (AMR) of neonatal bloodstream infections (BSIs) at 25 NICUs in eastern China, 2016-2019.Study designWe conducted a multicentre retrospective descriptive analysis of all positive blood cultures collected at 25 NICUs of tertiary hospitals between January 1, 2017, and December 31, 2019. ResultsFrom 1 January 2017 to 31 December 2019, a total of 1092 pathogenic bacteria isolates were met inclusion criteria among 66516 specimens. 349 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(39 reference statements)
2
0
0
Order By: Relevance
“…In the present study, the most common three gramnegative organisms for infections were Enterobacterium, Klebsiella pneumonia, and Escherichia coli, respectively, similar to the findings of previous studies (5,6,7,8). In contrast, Solomon showed that the most prevalent gramnegative bacterial species were Klebsiella spp, Escherichia coli, and Acinetobacter baumannii (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the most common three gramnegative organisms for infections were Enterobacterium, Klebsiella pneumonia, and Escherichia coli, respectively, similar to the findings of previous studies (5,6,7,8). In contrast, Solomon showed that the most prevalent gramnegative bacterial species were Klebsiella spp, Escherichia coli, and Acinetobacter baumannii (9).…”
Section: Discussionsupporting
confidence: 91%
“…Fifteen newborns in our study (14.4%) developed early-onset sepsis, and 53 (51%) developed late-onset sepsis. The overall mortality rates of gram-negative infections and MDR isolates were 4.7% vs. 4.3%, respectively, consistent with the report of Liu et al (4.4% for hospital-acquired late-onset sepsis, 7.4% for early sepsis) (8).…”
Section: Discussionsupporting
confidence: 90%